Eutectic gel as well as preparation method and application thereof

By polymerizing acrylamide monomer, acrylic monomer and crosslinking agent in a eutectic solvent, and adding cellulose nanocrystals, an eutectic gel was prepared, which solved the shortcomings of traditional conductive hydrogels in terms of environmental stability, mechanical properties and recyclability, and achieved high mechanical properties, excellent environmental stability and recyclability.

CN119775494AActive Publication Date: 2025-04-08天津大学浙江研究院

Patent Information

Application Number
CN202411976756.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-08
Estimated Expiration
2044-12-31

AI Technical Summary

Technical Problem

Traditional conductive hydrogels have shortcomings in environmental stability, mechanical properties and recyclability, limiting their practicality in diverse applications.

Method used

A eutectic gel was prepared by polymerizing acrylamide monomer, acrylic monomer and a crosslinking agent in a eutectic solvent and adding cellulose nanocrystals. The gel produces different interactions in the polymer-rich and solvent-rich phases, enhancing mechanical properties while maintaining environmental stability and recyclability.

Benefits of technology

The high mechanical properties of eutectic gels, excellent environmental stability and recyclability are achieved, enhancing their practicality in sensors and other applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119775494A_ABST
    Figure CN119775494A_ABST
Patent Text Reader

Abstract

The invention discloses eutectic gel as well as a preparation method and application thereof. The eutectic gel at least comprises a polymer obtained by polymerizing an acrylamide monomer, an acrylic monomer and a cross-linking agent in a eutectic solvent, and cellulose nanocrystals are also added into the polymer. The preparation method comprises the following steps: preparing the eutectic solvent; the preparation method comprises the following steps: at least adding an acrylamide monomer, an acrylic monomer, a cross-linking agent and cellulose nanocrystals into a deep-eutectic solvent, and uniformly mixing; and carrying out polymerization reaction to obtain the eutectic gel. According to the invention, two polymer monomers with different compatibility with the eutectic solvent are copolymerized to prepare the eutectic gel with phase separation, and meanwhile, the cellulose nanocrystal with different interaction with two phases in the eutectic gel is used as the flexibilizer, so that the mechanical property of the eutectic gel is effectively enhanced, and the mechanical property of the eutectic gel is improved. And the eutectic gel has temperature and strain dual response characteristics and good environmental stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of gel, and in particular relates to a eutectic gel, a preparation method thereof and an application thereof. Background Art

[0002] Ion-conductive hydrogels are a type of flexible material that has electrical conductivity through the migration of ions. They are usually composed of a three-dimensional cross-linked polymer network with a high water content and mobile ions. The ions in the hydrogel can come from an external electrolyte solution, an embedded ionic polymer, or a nanomaterial with ion conductivity. Conductive hydrogel materials have been widely used in wearable sensors, soft robots, and energy storage devices due to their high water content, excellent flexibility, and high conductivity. However, this type of hydrogel usually requires additional conductive components, which may weaken the interaction between polymers and further lead to a decrease in the mechanical properties of the hydrogel. In addition, conductive hydrogels also face poor environmental stability and potential ion leakage problems, which limits their practical applications.

[0003] Deep eutectic solvents are an emerging class of conductive liquids consisting of a eutectic mixture of hydrogen bond acceptors and hydrogen bond donors. In recent years, due to their high conductivity, non-toxicity, biodegradability and low cost, deep eutectic solvents have been gradually applied to the development of conductive deep eutectic gels to replace hydrogels. At present, a variety of deep eutectic gels with long-term stability and high conductivity have been prepared by in situ polymerization of monomers in deep eutectic solvents, showing great application potential in flexible electronic devices. The presence of deep eutectic solvents endows deep eutectic gels with good conductivity, environmental stability and antibacterial properties. However, most existing deep eutectic gels still face problems such as weak mechanical properties, limited functionality and non-recyclability. Therefore, it is necessary to explore a green and sustainable way to develop environmentally friendly, versatile and tough deep eutectic gels to enhance their practicality in diverse applications.

[0004] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention and should not be regarded as an acknowledgment or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art. Summary of the invention

[0005] The object of the present invention is to provide a eutectic gel, a preparation method and application thereof, which solve the problems of poor environmental stability, weak mechanical properties and non-recyclability of traditional gel sensors.

[0006] In order to achieve the above object, a technical solution provided by a specific embodiment of the present invention is as follows:

[0007] A eutectic gel, the eutectic gel comprising at least:

[0008] A polymer obtained by polymerizing acrylamide monomers, acrylic acid monomers and a cross-linking agent in a low eutectic solvent;

[0009] Cellulose nanocrystals are also added into the polymer.

[0010] In one or more embodiments of the present invention, the length of the cellulose nanocrystals is 50 to 200 nm.

[0011] In one or more embodiments of the present invention, the diameter of the cellulose nanocrystals is 5 to 20 nm.

[0012] In one or more embodiments of the present invention, the mass fraction of the cellulose nanocrystals in the eutectic gel is 5-20 wt %.

[0013] In one or more embodiments of the present invention, the molar ratio of the acrylic acid monomer to the acrylamide monomer is (0.3-3):1.

[0014] In one or more embodiments of the present invention, the molar ratio of the sum of the molar amounts of the acrylic monomers and acrylamide monomers to the sum of the molar amounts of the crosslinking agent and the low eutectic solvent raw material is 1:(0.001-0.003):(1-3).

[0015] In one or more embodiments of the present invention, the polymer raw material further includes a photoinitiator, and the molar ratio of the sum of the molar amounts of the acrylic monomer and the acrylamide monomer to the photoinitiator is 1:(0.002-0.05).

[0016] In one or more embodiments of the present invention, the raw material of the low eutectic solvent includes at least a hydrogen bond acceptor and a hydrogen bond donor, and the molar ratio of the hydrogen bond acceptor to the hydrogen bond donor is 1:(1-6).

[0017] Another specific embodiment of the present invention provides a technical solution as follows:

[0018] A method for preparing a eutectic gel comprises the following steps:

[0019] preparing a deep eutectic solvent;

[0020] At least acrylamide monomer, acrylic acid monomer, crosslinking agent and cellulose nanocrystals are added into a low eutectic solvent and mixed;

[0021] The polymerization reaction is carried out to obtain a eutectic gel.

[0022] Another specific embodiment of the present invention provides a technical solution as follows:

[0023] Application of eutectic gel in sensors.

[0024] Compared with the prior art, the present invention uses a low eutectic solvent as the liquid component of the gel to prepare a conductive low eutectic gel, which has the characteristics of good environmental stability compared with the existing conductive hydrogel; in addition, two polymer monomers with different compatibility with the low eutectic solvent are copolymerized to prepare a phase separation gel; at the same time, cellulose nanocrystals are used as a gel toughening agent, and the cellulose nanocrystals have different interactions with the two phases in the gel, which plays a role of selective toughening. In addition, the low eutectic gel prepared by the present invention has dual response characteristics of temperature and strain when used as a sensor. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0026] Figure 1 This is a scanning electron microscope photograph of the eutectic gel in Example 1 of the present invention;

[0027] Figure 2 Graph showing tensile strength-tensile elongation of the eutectic gel in Examples 1-4 of the present invention;

[0028] Figure 3 This is a graph of the elongation rate-resistance relative change rate of the eutectic gel in Example 1 of the present invention;

[0029] Figure 4 This is a temperature-resistance relative change rate diagram of the eutectic gel in Example 1 of the present invention;

[0030] Figure 5 This is a graph of tensile strength at break versus elongation at break of the eutectic gel in Example 1 of the present invention;

[0031] Figure 6 This is a graph showing the change in relative mass of the eutectic gel of Example 1 of the present invention over time. DETAILED DESCRIPTION

[0032] In order to enable those skilled in the art to better understand the technical solutions in the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

[0033] Although the low eutectic gels that have been developed have excellent properties, few reports focus on the use of green methods or materials to make low eutectic gels. Cellulose nanocrystals are biodegradable materials derived from nature with a highly crystalline structure, rich surface functional groups and a high aspect ratio. They are considered to be ideal reinforcing agents for gel materials. In hydrogel systems, the concentration of cellulose nanocrystals is often a key parameter affecting the mechanical properties of hydrogels. When the concentration of cellulose nanocrystals in water is high (usually more than 12wt%), cellulose nanocrystals tend to form aggregates due to their strong hydrogen bonding. These aggregates form a non-uniform network in the hydrogel, resulting in a decrease in mechanical strength. However, in low eutectic solvents, cellulose nanocrystals are not easy to form dense entanglements at high concentrations because the charged ions in the low eutectic solvents hinder the formation of hydrogen bonds between cellulose nanocrystals. Therefore, in the medium of low eutectic solvents, high-concentration cellulose nanocrystals can achieve uniform and stable dispersion, thereby more effectively exerting their reinforcing effect.

[0034] A specific embodiment of the present invention provides a low eutectic gel, which at least includes: a polymer obtained by polymerizing acrylamide monomers, acrylic acid monomers and a cross-linking agent in a low eutectic solvent; cellulose nanocrystals are also added to the polymer.

[0035] Specifically, the compatibility of acrylamide monomers and acrylic acid monomers in low eutectic solvents is different. The copolymerization of the two will induce phase separation of the gel, namely, a polymer-rich phase (polyacrylamide phase) and a solvent-rich phase (polyacrylic acid phase). The introduction of cellulose nanocrystals into the low eutectic gel can produce different interactions in the polymer-rich phase and the solvent-rich phase: the cellulose nanocrystals can enhance the rigidity of the polymer-rich phase through hydrogen bonding interactions, while in the solvent-rich phase, their interactions with the polymer are limited, preventing the formation of hydrogen bonds. Therefore, the cellulose nanocrystals in the low eutectic gel can selectively enhance the polymer-rich phase and maintain the flexibility of the solvent-rich phase, thereby giving the low eutectic gel strong mechanical properties, including excellent toughness, fracture strength and Young's modulus. In addition, the presence of the low eutectic solvent gives the low eutectic gel excellent environmental stability and ionic conductivity. Moreover, since the strong hydrogen bonding between cellulose nanocrystals and water can destroy the gel network, the low eutectic gel can be recovered in water.

[0036] Furthermore, the length of the cellulose nanocrystals is 50 to 200 nm, and the diameter is 5 to 20 nm.

[0037] Specifically, the size of cellulose nanocrystals will affect their dispersion in the eutectic gel. If the size is too large, the cellulose nanocrystals will be unevenly dispersed in the eutectic gel, thereby hindering the polymerization of monomers and deteriorating the mechanical properties of the eutectic gel. If the size is too small, the mechanical properties of the cellulose nanocrystals will be poor and they will not be able to play a role in toughening the eutectic gel.

[0038] Furthermore, the mass fraction of cellulose nanocrystals in the eutectic gel is 5 to 20 wt %.

[0039] Specifically, by controlling the addition amount of fiber nanocrystals, the mechanical properties of the eutectic gel can be effectively enhanced.

[0040] Furthermore, the molar ratio of acrylic acid monomer to acrylamide monomer is (0.3-3):1, and the molar ratio of the sum of the molar amounts of acrylic acid monomer and acrylamide monomer to the sum of the molar amounts of the crosslinking agent and the low eutectic solvent raw material is 1:(0.001-0.003):(1-3).

[0041] Specifically, the crosslinking agent is N,N′-methylenebisacrylamide, the acrylamide monomer includes any one of acrylamide, methacrylamide and dimethylacrylamide or a combination of at least two thereof, and the acrylic monomer includes any one of acrylic acid, methacrylic acid and methyl methacrylate or a combination of at least two thereof. Polymerizing the acrylic monomer and the acrylamide monomer in a certain molar ratio can ensure that the obtained eutectic gel has good mechanical properties.

[0042] Furthermore, the polymerization raw material also includes a photoinitiator, and the molar ratio of the sum of the molar amounts of acrylic monomers and acrylamide monomers to the photoinitiator is 1:(0.002-0.05).

[0043] Specifically, the photoinitiator is one of 2-hydroxy-2-methyl-1-phenylpropanone, benzophenone and methyl benzoate. The crosslinker and the photoinitiator can promote the polymerization of acrylic monomers and acrylamide monomers. By controlling the molar ratio, the acrylic monomers and acrylamide monomers can be effectively polymerized to ensure that the formed eutectic gel has better mechanical properties.

[0044] Furthermore, the raw materials of the low eutectic solvent include at least a hydrogen bond acceptor and a hydrogen bond donor, and the molar ratio of the hydrogen bond acceptor to the hydrogen bond donor is 1:(1-6).

[0045] Specifically, the hydrogen bond acceptor is one or more of quaternary ammonium salts, amines and organic acid salts; the hydrogen bond donor is one or more of carboxylic acids and polyols. By controlling the molar ratio of the hydrogen bond acceptor and the hydrogen bond donor, the eutectic gel has good mechanical properties.

[0046] Another specific embodiment of the present invention provides a method for preparing a eutectic gel, comprising steps 1-3.

[0047] Step 1, prepare a deep eutectic solvent.

[0048] Specifically, the hydrogen bond acceptor and the hydrogen bond donor are mixed in a molar ratio of 1:(1-6), heated to 80-90° C. for 5-8 min, and heated until the solution is clear and transparent to obtain a low eutectic solvent.

[0049] Step 2: adding at least acrylamide monomers, acrylic acid monomers, a crosslinking agent and cellulose nanocrystals into a low eutectic solvent and mixing them evenly.

[0050] Specifically, acrylamide monomers, acrylic acid monomers, N,N'-methylenebisacrylamide, photoinitiator, cellulose nanocrystals and low eutectic solvent are uniformly mixed to obtain a gel prepolymer solution. The molar ratio of acrylic acid monomers to acrylamide monomers is (0.3-3):1, the molar ratio of the sum of the molar amounts of acrylic acid monomers and acrylamide monomers, N,N'-methylenebisacrylamide, photoinitiator and low eutectic solvent, i.e., the sum of the molar amounts of hydrogen bond acceptors and hydrogen bond donors is 1:(0.001-0.003):(0.002-0.05):(1-3), and the mass fraction of cellulose nanocrystals in the gel prepolymer solution is 5-20wt%.

[0051] Step 3, performing a polymerization reaction to obtain a eutectic gel.

[0052] Specifically, the gel prepolymer solution is irradiated with 365 nm ultraviolet light for 10-20 minutes.

[0053] Another specific embodiment of the present invention provides the use of the above eutectic gel in a sensor.

[0054] Specifically, the eutectic gel in the present invention can be directly used as a sensor, which can sense mechanical strain and temperature changes and has great application potential in environmentally friendly high-performance electronic devices.

[0055] The present invention is further described in detail below in conjunction with specific embodiments.

[0056] The cellulose nanocrystals used in the present invention were purchased from Beijing Shansi Technology Co., Ltd.

[0057] Example 1

[0058] Eutectic gel was prepared as follows:

[0059] (1) Ammonium phosphate and ethylene glycol are uniformly mixed in a molar ratio of 1:5, and the mixed solution is heated at 80° C. for 8 minutes to obtain a low eutectic solvent.

[0060] (2) Adding acrylamide, acrylic acid, N,N′-methylenebisacrylamide, 2-hydroxy-2-methyl-1-phenylpropanone, and cellulose nanocrystals to the low eutectic solvent obtained in step (1) and mixing them uniformly to obtain a gel prepolymer solution; wherein the molar ratio of acrylic acid to acrylamide is 3:1, and the molar ratio of the sum of the molar amounts of acrylic acid and acrylamide, N,N′-methylenebisacrylamide, 2-hydroxy-2-methyl-1-phenylpropanone and the low eutectic solvent is 1:0.001:0.005:3; and the mass fraction of the cellulose nanocrystals in the gel prepolymer solution is 5wt%.

[0061] (3) The gel prepolymer solution was irradiated with an ultraviolet lamp with a wavelength of 365 nm for 10 minutes to obtain a low-melting gel after solidification.

[0062] The scanning electron microscope image of the prepared eutectic gel is shown in Figure 1 As shown, it can be seen that the eutectic gel presents an obvious phase separation structure.

[0063] Example 2

[0064] Eutectic gel was prepared as follows:

[0065] (1) Ammonium chloride and lactic acid are uniformly mixed in a molar ratio of 1:4, and the mixed solution is heated at 90° C. for 5 min to obtain a deep eutectic solvent.

[0066] (2) adding methacrylamide, methacrylic acid, N,N′-methylenebisacrylamide, benzophenone, and cellulose nanocrystals to the low eutectic solvent obtained in step (1) and mixing them uniformly to obtain a gel prepolymer solution; wherein the molar ratio of methacrylamide to methacrylic acid is 2:1, and the molar ratio of the sum of the molar amounts of methacrylic acid and methacrylamide, N,N′-methylenebisacrylamide, benzophenone, and the low eutectic solvent is 1:0.002:0.006:3; and the mass fraction of the cellulose nanocrystals in the gel prepolymer solution is 10 wt %.

[0067] (3) The gel prepolymer solution was irradiated with an ultraviolet lamp with a wavelength of 365 nm for 8 minutes to obtain a low eutectic gel after solidification.

[0068] Example 3

[0069] Eutectic gel was prepared as follows:

[0070] (1) Urea and propylene glycol were mixed uniformly in a molar ratio of 1:3, and the mixture was heated at 85° C. for 6 min to obtain a low eutectic solvent.

[0071] (2) adding dimethylacrylamide, acrylic acid, N,N′-methylenebisacrylamide, methyl benzoate, and cellulose nanocrystals to the low eutectic solvent obtained in step (1) and mixing them uniformly to obtain a gel prepolymer solution; wherein the molar ratio of dimethylacrylamide to acrylic acid is 0.8:1, and the molar ratio of the sum of the molar amounts of dimethylacrylamide and acrylic acid, N,N′-methylenebisacrylamide, methyl benzoate, and the low eutectic solvent is 1:0.003:0.007:2; and the mass fraction of the cellulose nanocrystals in the gel prepolymer solution is 15 wt %.

[0072] (3) The gel prepolymer solution was irradiated with an ultraviolet lamp with a wavelength of 365 nm for 7 minutes to obtain a low eutectic gel after solidification.

[0073] Example 4

[0074] Eutectic gel was prepared as follows:

[0075] (1) Choline chloride and glycerol are uniformly mixed in a molar ratio of 1:2, and the mixture is heated at 83° C. for 7 minutes to obtain a deep eutectic solvent.

[0076] (2) adding acrylamide, methyl methacrylate, N,N′-methylenebisacrylamide, 2-hydroxy-2-methyl-1-phenylpropanone and cellulose nanocrystals to the low eutectic solvent obtained in step (1) and mixing them uniformly to obtain a gel prepolymer solution; wherein the molar ratio of acrylamide to methyl methacrylate is 0.3:1, and the molar ratio of the sum of the molar amounts of acrylamide and methyl methacrylate, N,N′-methylenebisacrylamide, 2-hydroxy-2-methyl-1-phenylpropanone and the low eutectic solvent is 1:0.003:0.008:1; and the mass fraction of the cellulose nanocrystals in the gel prepolymer solution is 20 wt%.

[0077] (3) The gel prepolymer solution was irradiated with an ultraviolet lamp with a wavelength of 365 nm for 7 minutes to obtain a low eutectic gel after solidification.

[0078] Comparative Example 1

[0079] The difference between this comparative example and Example 1 is that in step (2), the molar ratio of acrylamide to acrylic acid is 0.1:1, and the other operating parameters and process steps are exactly the same as those in Example 1.

[0080] Comparative Example 2

[0081] The difference between this comparative example and Example 1 is that in step (2), the molar ratio of acrylamide to acrylic acid is 5:1, and the other operating parameters and process steps are exactly the same as those in Example 1.

[0082] Comparative Example 3

[0083] The difference between this comparative example and Example 1 is that in step (2), no cellulose nanocrystals are added, and other operating parameters and process steps are exactly the same as those in Example 1.

[0084] Comparative Example 4

[0085] The difference between this comparative example and Example 1 is that in step (2), the mass fraction of cellulose nanocrystals is 1 wt %, and the other operating parameters and process steps are exactly the same as those in Example 1.

[0086] Comparative Example 5

[0087] The difference between this comparative example and Example 1 is that in step (2), the mass fraction of cellulose nanocrystals is 40 wt %, and the other operating parameters and process steps are exactly the same as those in Example 1.

[0088] Comparative Example 6

[0089] The difference between this comparative example and Example 1 is that in step (1), the mixed solution is heated at 60° C. for 8 min, and the other operating parameters and process steps are exactly the same as those in Example 1.

[0090] Comparative Example 7

[0091] The difference between this comparative example and Example 1 is that in step (1), the mixed solution is heated at 120° C. for 5 min, and the other operating parameters and process steps are exactly the same as those in Example 1.

[0092] Comparative Example 8

[0093] The difference between this comparative example and Example 1 is that in step (1), ammonium phosphate and ethylene glycol are mixed in a molar ratio of 1:0.5, and the other operating parameters and process steps are exactly the same as those in Example 1.

[0094] Comparative Example 9

[0095] The difference between this comparative example and Example 1 is that in step (1), ammonium phosphate and ethylene glycol are mixed in a molar ratio of 1:8, and other operating parameters and process steps are exactly the same as those in Example 1.

[0096] The mechanical properties, strain sensing properties, temperature sensing properties, recyclability, and environmental stability of the eutectic gels prepared in each embodiment and each comparative example were tested, and the testing methods are as follows:

[0097] (1) Mechanical property test: The eutectic gel sample was cut into dumbbell-shaped sample strips of 30 mm × 3 mm × 1.5 mm, and the sample was mounted in the fixture of the testing machine. The sample was stretched at a load speed of 20 mm / min until the stretched sample broke. The change in the tensile strength of the sample with the tensile elongation during the stretching process was recorded. The tensile strength-tensile elongation graphs of Examples 1-4 are shown in FIG. Figure 2 As shown. Record the tensile strength and elongation at break of the sample. Integrate the tensile strength-elongation curve, and the area under the curve is the toughness. The test results are shown in Table 1.

[0098] (2) Strain sensing performance test: The eutectic gel sample prepared in Example 1 was cut into dumbbell-shaped sample strips of 30 mm × 3 mm × 1.5 mm. The sample strips were mounted on a universal mechanical testing machine and connected to a digital source meter. While the universal mechanical testing machine was stretching the sample, the digital source meter was used to record the change in resistance and plotted as shown below. Figure 3 The stretch rate-resistance relative change rate diagram shown. Figure 3 It can be seen that the relative change rate of resistance of the eutectic gel changes linearly with the stretching rate.

[0099] (3) Temperature sensing performance test: The eutectic gel sample prepared in Example 1 was cut into sample strips of 30 mm × 3 mm × 1 mm. The sample strips were fixed on a heating table, and the sample temperature was gradually increased. At the same time, a digital source meter was used to record the change in sample resistance. The result was plotted as follows: Figure 4 The temperature-resistance relative change rate diagram shown is given by Figure 4 It can be seen that with the increase of temperature, the relative change rate of resistance of the eutectic gel gradually decreases.

[0100] (4) Recyclability test: The eutectic gel prepared in Example 1 was cut into small pieces and dispersed in water. After ultrasonic treatment, a gel dispersion was obtained. The gel dispersion was poured into a mold and dried to obtain the recycled eutectic gel. The mechanical properties of the recycled eutectic gel were tested according to the test method (1). Figure 5 The tensile breaking strength-breaking elongation graph is shown.

[0101] (5) Environmental stability test: The eutectic gel prepared in Example 1 was placed in an indoor environment for 30 days, and the mass change of the eutectic gel was recorded. Figure 6 Shown is a graph of relative gel mass change versus time.

[0102] Table 1 Mechanical properties test results

[0103]

[0104]

[0105] Combined with Table 1, comparing Example 1, Comparative Example 1 and Comparative Example 2, the molar ratio of acrylamide monomer to acrylic acid monomer in Comparative Example 1 is too low, while the molar ratio of acrylamide monomer to acrylic acid monomer in Comparative Example 2 is too high, both of which will lead to a decrease in the mechanical properties of the obtained eutectic gel. In Example 1, the molar ratio of acrylamide monomer to acrylic acid monomer is within the preferred range provided by the present invention, and the prepared eutectic gel sensor has good mechanical properties.

[0106] Comparing Examples 1, 3, 4 and 5, no cellulose nanocrystals were added in Example 3, the amount of cellulose nanocrystals added in Example 4 was too low, and the amount of cellulose nanocrystals added in Example 5 was too high, all of which resulted in decreased mechanical properties of the obtained eutectic gel. In Example 1, the amount of cellulose nanocrystals added was within the preferred range provided by the present invention, and the prepared eutectic gel sensor showed good mechanical properties.

[0107] Comparing Example 1, Comparative Example 6 and Comparative Example 7, the heating time of the low eutectic solvent in Comparative Example 6 is too short, while the heating time in Comparative Example 7 is too long, both of which will lead to a decrease in the mechanical properties of the prepared low eutectic gel. However, the heating time of the low eutectic solvent in Example 1 is within the preferred range provided by the present invention, and the prepared low eutectic gel exhibits good mechanical properties.

[0108] Comparing Example 1, Example 8 and Example 9, the ratio of hydrogen bond donors in the low eutectic solvent in Example 8 is too low, while the ratio of hydrogen bond donors in the low eutectic solvent in Example 9 is too high, both of which will lead to a decrease in the mechanical properties of the prepared low eutectic gel. In Example 1, the ratio of hydrogen bond donors in the low eutectic solvent is within the preferred range provided by the present invention, and the prepared low eutectic gel sensor exhibits good mechanical properties.

[0109] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered exemplary and non-limiting in all respects, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations falling within the meaning and scope of the equivalent elements of the claims be included in the invention. Any reference numeral in a claim should not be considered as limiting the claim to which it relates.

[0110] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A eutectic gel, characterized in that: The eutectic gel at least comprises: A polymer obtained by polymerizing acrylamide monomers, acrylic acid monomers and a cross-linking agent in a low eutectic solvent; Cellulose nanocrystals are also added into the polymer.

2. The eutectic gel according to claim 1, characterized in that: The length of the cellulose nanocrystal is 50 to 200 nm.

3. The eutectic gel according to claim 1, characterized in that: The diameter of the cellulose nanocrystal is 5 to 20 nm.

4. The eutectic gel according to claim 1, characterized in that: The mass fraction of the cellulose nanocrystals in the eutectic gel is 5 to 20 wt %.

5. The eutectic gel according to claim 1, characterized in that: The molar ratio of the acrylic acid monomer to the acrylamide monomer is (0.3-3):

1.

6. The eutectic gel according to claim 1, characterized in that: The molar ratio of the sum of the molar amounts of the acrylic acid monomer and the acrylamide monomer to the sum of the molar amounts of the crosslinking agent and the low eutectic solvent raw material is 1:(0.001-0.003):(1-3).

7. The eutectic gel according to claim 1, characterized in that: The polymerization raw material also includes a photoinitiator, and the molar ratio of the sum of the molar amounts of the acrylic monomer and the acrylamide monomer to the photoinitiator is 1:(0.002-0.05).

8. The eutectic gel according to claim 1, characterized in that: The raw materials of the low eutectic solvent at least include a hydrogen bond acceptor and a hydrogen bond donor, and the molar ratio of the hydrogen bond acceptor to the hydrogen bond donor is 1:(1-6).

9. A method for preparing a eutectic gel, characterized in that: The steps include: preparing a deep eutectic solvent; At least acrylamide monomer, acrylic acid monomer, crosslinking agent and cellulose nanocrystals are added into a low eutectic solvent and mixed; The polymerization reaction is carried out to obtain a eutectic gel.

10. Use of the eutectic gel according to any one of claims 1 to 8 or the eutectic gel prepared by the method for preparing the eutectic gel according to claim 9 in a sensor.

Citation Information

Patent Citations

  • Hemicellulose-based hydrogel based on eutectic solvent as well as preparation method and application of hemicellulose-based hydrogel

    CN114702697A

  • Preparation method and application of high-strength, high-toughness and tear-resistant eutectic gel

    CN114957724A

  • Preparation and application of cellulose nanocrystal reinforced composite gel for heavy metal ion adsorption

    CN115228443A

  • Self-healing, anti-freezing and self-adhesive conductive ion hydrogel with birefringence characteristic as well as preparation method and application of self-healing, anti-freezing and self-adhesive conductive ion hydrogel

    CN115368509A

  • Self-moisture-absorption eutectic polymer gel and application thereof

    CN117304396A

Cited By

  • High-barrier and high-transparency nanofiber composite film as well as preparation method and application thereof

    CN120025575A

  • Biological plastic based on cellulose ether eutectic solvent and synthetic method thereof

    CN120289712A

  • Supramolecular co-melt adhesive, preparation and application thereof, pigment-loaded supramolecular co-melt adhesive and application of pigment-loaded supramolecular co-melt adhesive

    CN120349573A